Organizational and legal principles of the State Bureau of Investigation activity in the system of law enforcement agencies of Ukraine - S. M. Gusarov; Ya. M. Lisoyvan (Bulletin of Kharkiv National University of Internal Affairs)
The place and role of the State Bureau of Investigation in the modern classification system of law enforcement agencies of Ukraine is analyzed. The essence of the definition of “law enforcement agencies” is established, and the peculiarities of their activities are analyzed. It has been noted that modern law enforcement bodies must be considered as state bodies that function in the general system of public authorities and perform, in accordance with current legislation, relevant functions in various fields of internal and external activity of the state, the purpose of which is to observe and implement the rights and freedoms of citizens, legality and law and order with compliance with the rules and procedures regulated by law within the limits of their competence.